Short-term inhibition of 11β-hydroxysteroid dehydrogenase type 1 reversibly improves spatial memory but persistently impairs contextual fear memory in aged mice. (April 2015) - Wheelan, Nicola; Webster, Scott P.; Kenyon, Christopher J.; Caughey, Sarah; Walker, Brian R.; Holmes, Megan C.; Seckl, Jonathan R.; Yau, Joyce L.W.
Abstract: High glucocorticoid levels induced by stress enhance the memory of fearful events and may contribute to the development of anxiety and posttraumatic stress disorder. In contrast, elevated glucocorticoids associated with ageing impair spatial memory. We have previously shown that pharmacological inhibition of the intracellular glucocorticoid-amplifying enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) improves spatial memory in aged mice. However, it is not known whether inhibition of 11β-HSD1 will have any beneficial effects on contextual fear memories in aged mice. Here, we examined the effects of UE2316, a selective 11β-HSD1 inhibitor which accesses the brain, on both spatial and contextual fear memories in aged mice using a vehicle-controlled crossover study design. Short-term UE2316 treatment improved spatial memory in aged mice, an effect which was reversed when UE2316 was substituted with vehicle. In contrast, contextual fear memory induced by foot-shock conditioning was significantly reduced by UE2316 in a non-reversible manner. When the order of treatment was reversed following extinction of the original fear memory, and a second foot-shock conditioning was given in a novel context, UE2316 treated aged mice (previously on vehicle) now showed increased fear memory compared to vehicle-treated aged mice (previously on UE2316). Renewal of the original extinguished fear memory triggered by exposure to a new environmental context may explain these effects. Thus 11β-HSD1 inhibition reverses spatial memory impairments with ageing while reducing the strength and persistence of new contextual fear memories. Potentially this could help prevent anxiety-related disorders in vulnerable elderly individuals. Highlights: Aged mice were treated with UE2316 using a vehicle-controlled crossover design. Short-term UE2316 treatment improves spatial memory in a reversible manner. Contextual fear memory retention was impaired with UE2316. Contextual fear memory effects persisted following reversal of treatment.